Stone rain: the strange case of nuclear folklore in Iran's post-1979 revolution major earthquakes. (2nd January 2022) - Papoli-Yazdi, Leila
ABSTRACT: Iran lies in an earthquake belt, and many Iranians have highlighted memories of natural disasters. While visiting Bam, a city destroyed by a severe earthquake, my team and I realized that some inhabitants attribute the disaster to nuclear tests. These rumours were also heard from the survivors of the earthquake in Sarpol-e Zahab in 2018. Looking deeper into the roots of nuclear rumours, I found the origin of rumours about the unnatural cause of the earthquake many years earlier, before the 1979 revolution and in the Tabas 1978 disaster. In this article, the nuclear folklore around earthquakes in Iran has been investigated. Analysing public opinion about disasters without considering their perceptions, rumours, and folklore is not complete. The current study reveals an overlooked mechanism based on the long-term dictatorship and untrustful media have made understanding the disasters complicated in the country.